Geocaching w edukacji – przegląd międzynarodowych doświadczeń Część 1. Wprowadzenie: zalety i problemy - Referowska-Chodak, Ewa (Leśne Prace Badawcze, 2020)
This article discusses the advantages and challenges of geocaching in education, based on a literature review. The aim is to aid the implementation of similar methods for education in Poland, in particular in the field of forest education. The most important advantages of educational geocaching include: 1) going out to the field, including direct contact with nature, which promotes positive reception by the educated and helps to shape respect and responsibility towards the environment;2) enhancing enthusiasm and motivation to work brought about by the joy of searching for treasures, satisfaction from achievements and learning through play; 3) versatility including acquisition of multidisciplinary knowledge, developing skills, problem solving, combining theory and practice as well as physical activity. On the other hand, the problems one faces with the use of geocaching include a lack of knowledge and practice of most educators, fear and reluctance to change the traditional way of teaching, the laborious preparation of geocaching, limitations set by nature such as a short duration of some phenomena or dependence on the weather as well as the pressure on nature resulting from this educational method, which could cause or increase trampling of vegetation and erosion. In overall, due to the comprehensive advantages of educational geocaching, it should be more widely implemented in both formal and non-formal education in Poland. In the case of the latter, the extensive experience of, among others, foresters, employees of national parks or landscape parks in field education provides further support for geocaching as a useful educational tool. Anadditional supporting argument is the not always satisfactory effectiveness of already existing methods in teaching. Taking the experiences gathered in other countries into account, especially concerning potential risks and problems, as presented in this article, it is possible to take full advantage of geocaching as a tool or strategy in education, including forest education.